Case of fertility treatment‐induced Stevens‐Johnson syndrome with a severe ocular complication. Issue 11 (5th September 2019) - Hashimoto, Hiroyo; Miyachi, Hideaki; Kataoka, Koki; Maru, Yugo; Togawa, Yaei; Matsue, Hiroyuki
Abstract: Pharmacological regimens with multiple medications are being used in fertility treatments. Herein, we report a case of a 40‐year‐old Japanese woman who developed Stevens‐Johnson syndrome (SJS) with a severe ocular complication during fertility treatment. Despite early multimodal interventions, including methylprednisolone pulse therapy and plasma exchange, her ocular complications persisted for more than a year. The four drugs administered in this case (cabergoline, medroxyprogesterone acetate, clomiphene, and intravenous human chorionic gonadotropin) have never been reported to induce SJS. Based on this case, we suggest that obstetricians, gynecologists, and dermatologists should be aware of fertility treatment‐induced severe drug eruptions.